PERKAWINAN SEBAGAI SIMBOLISASI KONTROL SOSIAL TERHADAP PEREMPUAN - Sumbulah, Umi (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2008)
There are some marital regulation in Islam which are considered as gender bias such as the concept of wali, nusyuz, the practice of polygamy, right and obligation of the spouse. It does not only create various religious understanding which is gender bias but also create asymmetrical relation of which it results in various forms of gender inequality.In particular circumstances, children become vulnerable victims of fiqh as the law product of men's understanding and effort which are generated from what have been regulated in The Qur'an and Hadith under patriarchal socio-cultural and political setting. Nurture theory about social role of man and woman also contributes to marginalization and sub-ordination of woman in spouse relationship within the family. Â